Elyon : a lost book - Dekker, Ted, 1962- (Dekker, Ted, 1962- Lost books, 2009)
The Chosen Ones need Elyon's grace to face their greatest threat yet, but Darsal is torn between her new mission, trying to love the Horde as Elyon asked her to, and her original one, especially now that Johnis and Silvie no longer seem to be on her side.